Calcium plus magnesium indicates digestibility: the significance of the second major axis of plant chemical variation for ecological processes - Mládková, Pavla; Mládek, Jan; Hejduk, Stanislav; Hejcman, Michal; Pakeman, Robin J (Ecology letters, 2018)
Plant variation in nutrient concentrations encompasses two major axes. The first is connected to nitrogen (N) and phosphorus (P), reflects growth rate and has been designated as the leaf economics spectrum (LES) while the second follows the gradient in calcium (Ca) and magnesium (Mg) and mirrors cell structural differences. Here, we tested in grasslands whether the sum Ca + Mg concentrations is a better indicator of digestibility than LES constituents. Structural equation modelling revealed that the total effect size of N (0.30) on digestibility was much lower than that of Ca + Mg (0.58). The N effect originated predominantly from sampling date (biomass ageing), while the Ca + Mg effect largely from phylogenetic composition (proportion of monocots). Thus, plant variation in partially substitutable divalent cations seems to play a significant role in biomass digestion by ruminants. This finding contests, together with litter decomposition studies, the prominent role of the LES for understanding both fundamental ecological processes.
Keywords: rostliny; Calcium; Plant Physiological Phenomena; hořčík; Phylogeny; Nitrogen; listy rostlin; fyziologie rostlin; Plant Leaves; Plants; fylogeneze; Phosphorus; Magnesium; fosfor; dusík; vápník